2020
DOI: 10.1515/gps-2020-0051
|View full text |Cite
|
Sign up to set email alerts
|

In vitro bactericidal, antidiabetic, cytotoxic, anticoagulant, and hemolytic effect of green-synthesized silver nanoparticles using Allium sativum clove extract incubated at various temperatures

Abstract: The current research aimed to evaluate in vitro biological activities of green-synthesized silver nanoparticles using the Allium sativum clove extract. The stability of green-synthesized silver nanoparticles was evaluated via storage at 4°C, room temperature (37°C), and calcined at 300°C, 500°C, and 700°C. The antibacterial effect was evaluated using agar well, spread plate, biofilm reduction, and cell proliferation inhibition assays. The cytotoxic and antidiabetic effects were determined via brine shrimp leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(4 citation statements)
references
References 61 publications
(68 reference statements)
0
4
0
Order By: Relevance
“…Moreover, the hemolytic activity of the compounds could be variable and dependent on such factors as temperature, incubation period as well the composition of the plant extract. 62 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the hemolytic activity of the compounds could be variable and dependent on such factors as temperature, incubation period as well the composition of the plant extract. 62 …”
Section: Resultsmentioning
confidence: 99%
“…Our ndings are in correspondence with the other studies where it was demonstrated that some of the green-synthetized silver nanoparticles could induce hemolysis of erythrocytes in a dose-dependent manner. 61,62 Furthermore, it was demonstrated that lower doses (up to 5 mg mL −1 ) of AgNPs synthesized by using Catharanthus roseus didn't affect the stability of erythrocytes membrane, while the higher doses (10 mg mL −1 , 25 mg mL −1 , and 50 mg mL −1 ) exhibited a toxic effect on this cells 61,63 concluded that hemolysis of erythrocytes induced by AgNPs could be due to the direct Ag + and membrane interaction, thus forming reactive species and oxidative stress. Moreover, the hemolytic activity of the compounds could be variable and dependent on such factors as temperature, incubation period as well the composition of the plant extract.…”
Section: Hemolytic Activitymentioning
confidence: 99%
“…54 Likewise, the mycosynthesized AgNPs in the range of 5 to 20 nm with prominently spherical morphology showed 44.24 ± 0.64% alpha-amylase inhibition at the concentration of 0.5 mg mL −1 . 55 Alternatively, the biosynthesized spherical-shaped AgNPs from the leaf extract of Solanum khasianum with an average size of 15.96 nm showed 79.56% alpha-amylase inhibition at the concentration of 1 mg mL −1 . 56 In another study, the spherical-shaped AgNPs were fabricated in the range of 10.34 to 22.12 nm by using the leaf extract of Muntingia calabura .…”
Section: Resultsmentioning
confidence: 99%
“…Apart from this, many of the nanocomposites of silver in combination with natural products have been found to possess potential therapeutic applications. Anticancer, antidiabetic, anti-inflammatory, and antimicrobial activities are some of the few identified applications [4,13,[22][23][24].…”
Section: Introductionmentioning
confidence: 99%